Redefining the costal margin: A pilot study. Issue 6 (19th December 2022) - Laswi, Mujahed; Lesperance, Rich; Kaye, Adam; Bauman, Zachary; Hansen, Adam; Achay, Jennifer; Kubalak, Steven; Eriksson, Evert
Abstract : The costal margin consists of variability in the attachments of the 9th and 10th ribs. Contrary to classical anatomic teaching, the 10th rib is often floating and mobile. Some of these anatomic differences may predispose patients to experience slipped rib syndrome. Abstract : BACKGROUND: Classical teaching of rib anatomy contends that the false ribs (7th to 10th) fuse anteriorly to form the costal margin of the chest. Slipped rib syndrome consists of false rib subluxation into the thorax with symptomatic impingement of the intercostal nerve. We sought to determine the incidence of this anatomic finding through anatomic study of the costal margin. METHODS: Cadavers were evaluated for mobility and attachment of the ninth and tenth ribs. Experienced anatomists and chest wall surgeons conducted a standardized dissection and assessed rib tip mobility using predefined criteria. Videos of dissections were submitted to a single investigator who reviewed the findings. RESULTS: Costal margins of 40 cadavers (45% male) were evaluated bilaterally. The average age was 83 years ± 11 years. The ninth rib was found to be attached to the eighth rib 100% of the time by an interchondral cartilaginous attachment along the body of the eighth and ninth ribs. Internal subluxation was noted in 19% (15 of 80), and the tip of the rib was mobile in 86% (69 of 80) evaluations. The tenth rib was attached to the ninth rib in 18%(14/80). A "floating" 10th rib was noted in 59% (47 of 80) of specimens. Subluxation was noted in 33% (26 of 60). Half of the ribs that subluxed moved medially to the ninth rib and half moved externally. An upwardly hooked tip was noted in 10% (8 of 80). Ribs with a hooked tip subluxed in 63% (5 of 8), and all of these ribs (5 of 5) moved to the interior of the chest ( p = 0.020). CONCLUSION: The ninth rib is commonly attached to the eighth rib, but the tenth rib is often not attached to the ninth rib. Most commonly, the tenth rib is a "floating" rib. Internal subluxation of the tenth rib as well as the presence of a hooked tip may predispose individuals to the development of "slipped rib syndrome." LEVEL OF EVIDENCE: Diagnostic Tests or Criteria; Level III. Abstract :